2010
DOI: 10.1007/s11746-010-1673-z
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Protein Concentrates and Isolates Prepared from Oil Cakes Have High Water Solubility and Antioxidant Capacity

Abstract: Increasing the applications of industrial byproducts is of great interest. Therefore, in the present study, sunflower oil cake from a local oil manufacturing company was used to obtain soluble protein concentrates and isolates with different content of phenolic compounds. All the extraction procedures evaluated resulted in concentrates and isolates with water solubility higher than 75% but with different chemical composition, color and physicochemical properties (i.e. surface hydrophobicity, thermal stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 23 publications
9
63
1
2
Order By: Relevance
“…Possible protein (and fat) extraction rate c Aider and Barbana, 2011;DLG, 1997;Fischer et al, 2001;Salgado et al, 2011;Salgado et al, 2012;Shallo et al, 2001;Tan et al, 2011;Villanueva et al, 1999;Wang et al, 2005 Maize silage Potential starch extraction at different maturity stages b,c or harvested as maize grains a Baldwin et al, 1992;DLG, 1997;Stolp, 2004 a Identical factor for the human-edible fraction for protein and energy due to presumed usage of whole grain. b Two different factors for the human-edible fractions for protein and energy: human-edible fractions for protein are derived from the potential extraction rates for protein, whereas the human-edible fractions for energy are the sum of the amount of gross energy in the extractable starch and protein divided by the gross energy content of the feedstuff.…”
Section: Feedstuffmentioning
confidence: 99%
“…Possible protein (and fat) extraction rate c Aider and Barbana, 2011;DLG, 1997;Fischer et al, 2001;Salgado et al, 2011;Salgado et al, 2012;Shallo et al, 2001;Tan et al, 2011;Villanueva et al, 1999;Wang et al, 2005 Maize silage Potential starch extraction at different maturity stages b,c or harvested as maize grains a Baldwin et al, 1992;DLG, 1997;Stolp, 2004 a Identical factor for the human-edible fraction for protein and energy due to presumed usage of whole grain. b Two different factors for the human-edible fractions for protein and energy: human-edible fractions for protein are derived from the potential extraction rates for protein, whereas the human-edible fractions for energy are the sum of the amount of gross energy in the extractable starch and protein divided by the gross energy content of the feedstuff.…”
Section: Feedstuffmentioning
confidence: 99%
“…Thermal properties of sunflower protein isolates were determined using Differential Scanning Calorimetry (DSC Q100 V9.8 Build 296 New Castle, Del., USA) following the method adopted by Salgado et al (2011). Hermetically sealed aluminium pans containing 10-15 mg sunflower protein solution (20 % w/v) were scanned over a range of 20-120°C at a rate of 10°C/min.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Determination of protein products solubility were performed according to [30] using solutions with pH values from 2 to 10, adjusted with 1 N HCl or 1 N NaOH, and protein concentration 1 mg/1 ml. Prepared protein suspensions were mixed by shaker during 1 h. Suspensions were centrifuged for 30 min at 3,500g.…”
Section: Determination Of Proteins Functional Propertiesmentioning
confidence: 99%
“…At the same time it was shown that protein isolates, prepared from sunflower oil cake, had very high solubility (above 80% at pH 8) [30]. For this purpose authors had suspended isoelectric protein pellet in water at pH 9 and suspension was dried lyophilization.…”
Section: Technological Properties Of Oil Seeds Proteinsmentioning
confidence: 99%
See 1 more Smart Citation